Harun Farocki : working on the sightlines - Farocki, Harun; Elsässer, T. (Thomas) (Amsterdam University Press, 2004)
The first English-language book on Germany's 'best-known important filmmaker'.
Includes indexes.
Keywords: Farocki, Harun -- Criticism and interpretation.; Farocki, Harun; Motion picture producers and directors -- Germany -- Biography.; The arts.; Film, TV and radio.; PERFORMING ARTS -- Film & Video -- Direction & Production.; BIOGRAPHY & AUTOBIOGRAPHY -- Entertainment & Performing Arts.; Motion picture producers and directors; Germany; Humaniora -- Film.; Biographies; Criticism, interpretation, etc.; Biographies.